The poor prognosis of the primary gastric epithelioid angiosarcoma: A case report. Issue 15 (April 2018) - Xia, Jie; Shi, DiKe; Wu, ZhiWei; Chen, Yang; Liu, BaoQing; Chen, Li; Metta, Wongkamchai; Zheng, YiXiong
Abstract: Rationale: Primary gastric epithelioid angiosarcoma is a highly aggressive endothelial cell malignancy and may pose a great diagnostic challenge. Patient concerns: Here we describe the case of a 56-year-old man presented with melena and epigastric dull pain for 2 weeks. Diagnosis: Primary gastric epithelioid angiosarcomas: the definitive diagnosis was provided by immunohistochemical analysis with endothelial markers such as cluster of differentiation 31 (CD31), ether-a-go-go-related gene (ERG), and Freund leukemia integration (FLI-1). Interventions: After gastroscopic biopsy was performed at the bleeding fundus and the results suggested malignant tumor, radical gastrectomy was performed. Outcomes: Unfortunately, regional lymph node enlargement and distant metastases occurred about 1 month later. The patient did not have the opportunity to undergo chemotherapy or other treatment and died from multiple organ dysfunction syndrome. Lessons: Primary gastric epithelioid angiosarcomas are rare tumors with a high rate of lymph nodes and peripheral organs metastasis. The strong cytokeratin expression in epithelioid angiosarcomas represents a diagnostic pitfall for pathologists. Their clinical behaviors are unpredictable and results with surgical excision alone have been disappointing. Thus, the prognosis is generally considered poor and patients seldom can survive over 1 year after diagnosis.